2018
DOI: 10.1590/abd1806-4841.20186807
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of wheal and flare in histamine test by the main H1 antihistamines commercialized in Brazil

Abstract: BackgroundSeveral dermatoses are mediated by histamine, such as urticaria, angioedema, and papular urticaria. There are no Brazilian studies comparing the potency of antihistamines.ObjectivesTo evaluate the tolerability and efficacy of the main commercial brand and generic H1 antihistamines, regarding the suppression of the wheal and flare to the histamine test.MethodsA quasi-experimental, open study with 10 healthy adults submitted to the histamine test on the ventral aspect of the forearms. After 20 minutes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…A recent meta-analysis performed by Huang et al, found that antihistamine effect of fexofenadine HCl was significantly higher than that of placebo (p < 0.00001, both flare and wheal), and non-inferior to other second-generation antihistamines (flare, p = 0.84; wheal, p = 0.21) based on the analysis of five studies on healthy subjects [ 64 ]. In a recent study conducted in Brazil, 10 healthy adults were subjected to the histamine test to compare the effect of the H 1 -antihistamines most used in the local clinical practice (dexchlorpheniramine, hydroxyzine, levocetirizine, fexofenadine HCl, cetirizine, loratadine, ebastine, desloratadine, epinastine and rupatadine) [ 65 ]. Two hours after intake, all antihistamines including fexofenadine HCl resulted in a significant reduction in the wheal (p < 0.02) as well as in the flare compared to control [ 65 ].…”
Section: Therapeutic Efficacy Of Fexofenadine Hclmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis performed by Huang et al, found that antihistamine effect of fexofenadine HCl was significantly higher than that of placebo (p < 0.00001, both flare and wheal), and non-inferior to other second-generation antihistamines (flare, p = 0.84; wheal, p = 0.21) based on the analysis of five studies on healthy subjects [ 64 ]. In a recent study conducted in Brazil, 10 healthy adults were subjected to the histamine test to compare the effect of the H 1 -antihistamines most used in the local clinical practice (dexchlorpheniramine, hydroxyzine, levocetirizine, fexofenadine HCl, cetirizine, loratadine, ebastine, desloratadine, epinastine and rupatadine) [ 65 ]. Two hours after intake, all antihistamines including fexofenadine HCl resulted in a significant reduction in the wheal (p < 0.02) as well as in the flare compared to control [ 65 ].…”
Section: Therapeutic Efficacy Of Fexofenadine Hclmentioning
confidence: 99%
“…In a recent study conducted in Brazil, 10 healthy adults were subjected to the histamine test to compare the effect of the H 1 -antihistamines most used in the local clinical practice (dexchlorpheniramine, hydroxyzine, levocetirizine, fexofenadine HCl, cetirizine, loratadine, ebastine, desloratadine, epinastine and rupatadine) [ 65 ]. Two hours after intake, all antihistamines including fexofenadine HCl resulted in a significant reduction in the wheal (p < 0.02) as well as in the flare compared to control [ 65 ]. Fexofenadine HCl 180 mg compared with desloratadine 5 mg significantly reduced histamine-induced flares (61% versus + 2%, respectively: p < 0.05) and wheals (p < 0.05) at 2 h after treatment in adults and adolescents [ 66 ].…”
Section: Therapeutic Efficacy Of Fexofenadine Hclmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-oxidant effects are most likely related, in addition to the photoprotective effects of Delphinol® [26] because anthocyanins can suppress allergic inflammatory responses in mast cells [40]. Released histamine induces skin flare [41]. The anti-oxidant effects of Del-phinol® are involved because oxidative stress induces skin inflammation [42] and redness.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine plays important physiological roles mediated through three histamine receptors, H1, H2 and H3, which belong to G protein-coupled receptors [19]. The H1 receptor is a representative histamine receptor that causes urticaria, and mediates wheal formation and vascular permeability [20,21]. Histamine is a relevant vasoactive derived from mast-cell degranulation, and the H1 receptor leads to vasodilatation and enhances blood flow [22].…”
Section: Histamine-mediated Mechanism As Ige-mediated Angioedemamentioning
confidence: 99%